2015
DOI: 10.1111/jbi.12679
|View full text |Cite
|
Sign up to set email alerts
|

Range‐wide phylogeography of the four‐toed salamander: out of Appalachia and into the glacial aftermath

Abstract: AimWe assessed the phylogeography of Hemidactylium scutatum across the entire range of the species, quantifying the diversity of populations, and identifying extrinsic factors that may have generated observed patterns of genetic connectivity and distribution.Location North America. MethodsWe performed DNA sequence analysis of the mitochondrial cytochrome oxidase 1 gene of 335 samples collected from 79 field locations distributed throughout the species range. Phylogenetic analyses, patterns of haplotype distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 42 publications
3
29
1
Order By: Relevance
“…Figure 3); however, this relationship was not significant. Further, previous studies of CIH caudates identified the Arkansas River Valley to be a phylogeographic barrier between the Ozarks and Ouachitas(Herman & Bouzat, 2016;Martin et al, 2016); however, the Arkansas River Basin was not a phylogeographic barrier for A. annulatum in our study.Although we surveyed a number of sites in the Ouachitas, we were only able to obtain a limited number of individuals and we were only able to obtain >10 individuals at one sampling site. Further, previous studies of CIH caudates identified the Arkansas River Valley to be a phylogeographic barrier between the Ozarks and Ouachitas(Herman & Bouzat, 2016;Martin et al, 2016); however, the Arkansas River Basin was not a phylogeographic barrier for A. annulatum in our study.Although we surveyed a number of sites in the Ouachitas, we were only able to obtain a limited number of individuals and we were only able to obtain >10 individuals at one sampling site.…”
contrasting
confidence: 86%
“…Figure 3); however, this relationship was not significant. Further, previous studies of CIH caudates identified the Arkansas River Valley to be a phylogeographic barrier between the Ozarks and Ouachitas(Herman & Bouzat, 2016;Martin et al, 2016); however, the Arkansas River Basin was not a phylogeographic barrier for A. annulatum in our study.Although we surveyed a number of sites in the Ouachitas, we were only able to obtain a limited number of individuals and we were only able to obtain >10 individuals at one sampling site. Further, previous studies of CIH caudates identified the Arkansas River Valley to be a phylogeographic barrier between the Ozarks and Ouachitas(Herman & Bouzat, 2016;Martin et al, 2016); however, the Arkansas River Basin was not a phylogeographic barrier for A. annulatum in our study.Although we surveyed a number of sites in the Ouachitas, we were only able to obtain a limited number of individuals and we were only able to obtain >10 individuals at one sampling site.…”
contrasting
confidence: 86%
“…Vertebrate examples are numerous in salamanders (e.g. Weisrock & Larson, 2006;Kozak & Wiens, 2010;Herman & Bouzat, 2016), whereas arthropod examples include other harvestmen (Thomas & Hedin, 2008;Hedin & Thomas, 2010), spiders (Hedin, 1997(Hedin, , 2001Hendrixson & Bond, 2005;Keith & Hedin, 2012;Hedin et al, 2015) and others. Also, intraspecific phylogeographical fragmentation is evident within more wide-ranging species, with many taxa including divergent populations on distinct massifs, separated by lowland riverine barriers.…”
Section: Introductionmentioning
confidence: 99%
“…The results we see in the case of E. lucifuga suggest that mitochondrial gene loci reflects a more ancient evolutionary history, wherein the central and eastern/western lineages diverged during the climatic shifts of the Pleistocene, possibly taking refuge in two locations as has been seen in other species (Phillips 1994;Zamudio and Savage 2003;Herman and Bouzat 2015). However, following expansion from Pleistocene refugia and establishment in present-day localities, there may have been secondary contact between central and eastern populations leading to introgression seen in the microsatellites and the POMC gene trees.…”
Section: Discussionmentioning
confidence: 62%
“…The sharing of haplotypes among localities in concert with the departures from neutrality we observe in estimates of Tajima's D and Fu's F and reduced nucleotide diversity suggests further recent expansion within the eastern and western regions. Lineage divergence during the turbulent Pleistocene reflects what we know about other North American salamanders (Church et al 2003;Herman and Bouzat 2015;Newman and Austin 2015) as well as other cave-dwelling species (Niemiller et al 2013;Bryson et al 2014), and in particular, other troglophilic salamanders (Cimmaruta et al 2015;Kuchta et al 2016). However, this estimation is much more recent than the dispersal event predicted by Martin et al (2015), which they estimated to have occurred approximately 4 Ma.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation